ANALISIS EVALUASI RENCANA DAN PENGENDALIAN JUMLAH PENGGUNAAN ANGGARAN BIAYA PELAKSANAAN PROYEK PEMBANGUNAN GEDUNG KANTOR PELAYANAN MASYARAKAT DINAS BINA MARGA DAN CIPTA KARYA PROV. JATENG - Ari Mahfud; Dina Citra Rosdiana; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
The Construction Project for the Public Service Office Building for the Highways and Human Settlements Office of Central Java Province is carried out from February to October 2021, with total contract value of Rp. 8,313,888,968. This project using planning and controlling time and costs so that later work will be more efficient, according to plans and objectives. The purpose of this study is to determine the time performance of the Development Project, to find out the problems encountered in the implementation of the Project, as well as the solutions used to overcome the problems that arise. The method used in this study is the Earned Value Concept method in which it combines elements of schedule, cost, and work performance to calculate the estimated cost and time needed to complete the project to completion. The data obtained from the Project includes the Budget Plan (RAB), Project Work Schedule, Daily, Weekly, Monthly Reports and actual cost requirements. Furthermore, an analysis of costs, schedules, and work performance is carried out by explaining the problems that arise during the research. From the results of the research and analysis it is known that the total costs incurred are relatively the same as the budget that has been planned, this is indicated by the results of CV = 1 and the project implementation time has been delayed from the planned schedule, indicated by the results of SPI = 6.6883 The results of calculating an estimated cost of Rp. 8,313,888,968 with an estimated completion time of 36 weeks which indicates a delay of 1 week from the planned 35 weeks. Where this delay was caused by several factors such as weather conditions which were in the rainy season when the project was running, damage or inadequate tools.